Beyond Content Transmission: Assessing the Pedagogical Alignment of Sensitive Historical Narratives (G30S/PKI) with OBE's Higher-Order Thinking Objectives in Indonesian Curriculum - Burhanuddin, Burhanuddin; Nasution, Bincar (Jurnal Mamangan, 2025)
This quantitative study examines the pedagogical alignment between traditional content transmission methods and Outcome-Based Education (OBE) approaches in teaching sensitive historical narratives, specifically the G30S/PKI incident, within Indonesian secondary education. The research investigates how effectively current pedagogical practices align with OBE's higher-order thinking objectives and their impact on students' critical thinking development. Using a survey research design, data were collected from 240 history teachers across urban, suburban, and rural schools in Indonesia through structured questionnaires and standardized assessment instruments. The findings reveal a significant misalignment between traditional content-focused teaching methods and OBE's higher-order thinking objectives, with 65% of teachers employing single official narrative approaches that scored low on pedagogical alignment indices (M = 0.52). Post-implementation analysis of OBE-aligned approaches demonstrated substantial improvements in students' higher-order thinking skills across all dimensions, with effect sizes ranging from 1.08 to 1.78 (p < 0.001). The study concludes that transitioning from content transmission to competency-based pedagogical approaches significantly enhances students' critical thinking capabilities while addressing sensitive historical topics more effectively. These findings have important implications for curriculum reform and teacher professional development in Indonesian history education